Maintaining Telomeres without Telomerase in Drosophila: Novel Mechanisms and Rapid Evolution to Save a Genus. - Cacchione, S.; Cenci, G.; Dion-Côté, A.M.; Barbash, D.A.; Raffa, G.D. (Cold Spring Harbor perspectives in biology, 2025)
Telomere maintenance is crucial for preventing the linear eukaryotic chromosome ends from being mistaken for DNA double-strand breaks, thereby avoiding chromosome fusions and the loss of genetic material. Unlike most eukaryotes that use telomerase for telomere maintenance, Drosophila relies on retrotransposable elements-specifically HeT-A, TAHRE, and TART (collectively referred to as HTT)-which are regulated and precisely targeted to chromosome ends. Drosophila telomere protection is mediated by a set of fast-evolving proteins, termed terminin, which bind to chromosome termini without sequence specificity, balancing DNA damage response factors to avoid erroneous repair mechanisms. This unique telomere capping mechanism highlights an alternative evolutionary strategy to compensate for telomerase loss. The modulation of recombination and transcription at Drosophila telomeres offers insights into the diverse mechanisms of telomere maintenance. Recent studies at the population level have begun to reveal the architecture of telomere arrays, the diversity among the HTT subfamilies, and their relative frequencies, aiming to understand whether and how these elements have evolved to reach an equilibrium with the host and to resolve genetic conflicts. Further studies may shed light on the complex relationships between telomere transcription, recombination, and maintenance, underscoring the adaptive plasticity of telomeric complexes across eukaryotes.